Rancang Bangun Aplikasi E-Commerce Berbasis Web Pada Toko Vapein - Sutrisno, Juan Pahlevy; Anwar, Nizirwan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2023)
In this era of rapid technological development, business people are required to keep up with thetimes so they can compete with other business people. With the existence of Covid-19, businesspeople are required to utilize information technology because business activities are hamperedby a ban on face-to-face meetings which has the potential to spread the virus. The researcheraims to create an e-commerce website for buying and selling vapes to increase vape sales thatare affected by the Covid-19 virus. Researchers use the waterfall method in building this vape ecommercewebsite because it has the advantage of working on a structured project, stage bystage so as to minimize errors that may occur. From the results of data analysis carried out byresearchers, it was found that standard system requirements, namely the existence of postageand automatic payments. The result of this research is that the VapeIn website can reach a widerrange of customers and the data reports are better managed